Metode Finger Painting Sebagai Upaya Mengurangi Temperament Pada Anak Usia Sekolah Akibat School From Home di SDN Kotalama 4 Malang - Dian Pitaloka Priasmoro; Indari; Ichwatus Saniah; Yusdianto Widodo; Dian Ayu Puspita (Pelita Abdi Masyarakat, 2021)
Background : Temperament is a condition in which a child is easily disturbed emotionally accompanied by the emergence of various expressions. Doing finger painting can help children sit still for 5 minutes or so, so that they can express their feelings and calm their emotions. Method : The first method used in this service is to increase children's knowledge about temperament and their impact on children. Then the second service team invited the children to do finger painting. Where grade 1 students are asked to make free or abstract pictures with their fingers. Then make regular lines such as curved lines, rectangles, triangles, zig zags and the last step is to give students the opportunity to sketch free images according to their imagination and color them with color paint using 5 fingers or palms. Result : A total of 27 students in grade 1 were able to understand the knowledge of temperament, characteristics, causes and ways to overcome temperament. All students can follow the procedure, follow from the beginning to the end of the activity, and feel the pleasure of getting a new learning experience that is different from usual through the finger painting program guided by the group leader. Conclusion : Based on the above results, it is hoped that the school will always provide creative and interesting learning experiences to students so that students do not experience boredom which can trigger temperament.